ZUM SPRICHWORTGEBRAUCH VON KINDERN UND JUGENDLICHEN: EINE EMPIRISCHE STUDIE AN REGIONALSCHULEN DER HANSESTADT ROSTOCK - Scheelke, Anne-Marthe (Proverbium - Yearbook, 2011)
Proverbs as a traditional component of language are part of everyone’s life. There has been a link between proverbs and school for centuries which still seems to exist, even though proverbs aren’t necessarily a curricular topic in modern schools. This paper deals with the usage of proverbs in German secondary schools. It checks if children and teenagers know common proverbs and anti-proverbs and tries to evaluate if they create new proverbs. The empirical study consists of a random sample of 200 fifth, seventh and ninth graders. The results show that proverbs are still known and common with todays youth. A special finding is the fact that former best known proverbs don’t seem to be the most famous with the 10-17 year olds. Especially the shifting of the number one proverb Morgenstund hat Gold im Mund is surprising